Enhancing Student Scientific Literacy on Competence Aspect Through Flipchart Media: A Development Study on Human Respiratory System Learning - Hanifa Mawaddah; Rasyidah Rasyidah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The level of science literacy among junior high school students regarding the human respiratory system remains low, as abstract concepts are difficult to grasp due to the limited learning media provided by teachers. This study aims to develop science literacy-based flipchart media to improve the scientific competence of eighth-grade students at MTsS Al-Washliyah Sei Langgei. Methodology: Using the Research and Development (R&D) framework, the study followed the 4D sequence of Define, Design, Develop, and Disseminate. Subject and media experts, science educators, and 24 students from seventh grade participated in this research. Data collected through expert validation forms, teacher and student practicality questionnaires, and pretest–posttest assessments. The data were analyzed quantitatively through validation percentages and N-Gain to assess effectiveness, as well as qualitatively through descriptive narratives of the comments and suggestions of experts and teachers. Findings: The results showed that the flipchart was highly valid (subject matter experts 96.43%; media experts 98.44%), highly practical (teachers 96.59%; students 98.13%), and effective (N-Gain 0.71). Contribution: These findings confirm that science literacy-based flipcharts are effective in improving students' conceptual understanding and scientific skills, facilitate teachers in delivering material, and can be used as an alternative medium and reference for the development of other science learning media